Innovation Management of Madrasah Aliyah Negeri Religious Program in Indonesia - Selamet Selamet; Jaja Jahari; Asep Nursobah; Agus Abdul Rahman (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The problem of this research departs from the phenomenon of declining quality of management of Madrasah Aliyah Negeri Religious Program (MANPK). There was a decline in the gap from the initial period of establishment of MANPK programs that were truly managed, taken seriously, with strict selection and adequate funding (project supported). While currently MANPK governance is more dependent on the standard implementation guidelines, innovation in each MANPK still occurs inequality between one MANPK and another. This research uses a qualitative approach, with a case study method with a multicluster multiple-case design type on three MANPKs, namely MAN 1 Darussalam Ciamis, MAN 1 Yogyakarta and MAN 1 Surakarta as research subjects. Data collection techniques were conducted through interviews, observation and documentation analysis. The data analysis technique uses the Miles and Huberman analysis technique. While the validity test was carried out by conducting tests; credibility, transferability, dependability, and confirmability. The results of the study found that: a) innovation planning in the form of innovation programs considers various aspects, with the steps of formulating goals, background, implementation, outcomes, benefits and evaluation of innovation programs. b) organizing madrasah innovation by determining goals, allocating programs, compiling program governance and resources. c) implementing innovations in the form of policy socialization, coordination, distribution of superior MAN religious program innovations, actualization of innovations carried out by internalizing superior programs in the curriculum, tutorial programs, self-development and extracurricular programs. d) evaluating madrasah innovation by determining the standards of innovation achievements that are poured into madrasah education standards.